From ADHD symptoms to parental stress: The roles of functional impairment, family functioning, and parental ADHD - Nitchawan Jongrakthanakij; Thanavadee Prachason; Nida Limsuwan; Komsan Kiatrungrit; Masatha Thongpan; Passaporn Lorterapong; Pattarabhorn Wisajun; Sudawan Jullagate (PLoS ONE, 2026)
Background Raising a child with Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with significant parental stress. However, the complex relationships between factors in the child and family in shaping this stress are not well understood. This study aimed to elucidate these interrelationships and identify the key determinants of parental stress. Methods A cross-sectional study included 127 children and adolescents with ADHD (70.9% males; mean age 9.6 ± 3.3 years) and their caregivers, recruited from the ADHD Registry at Ramathibodi Hospital, Bangkok (2019–2023). Caregivers completed standardized measures of parental stress, child ADHD symptoms, child functional impairment, family functioning, and parental ADHD symptoms. Structural equation modeling was used to examine pathways from child and parental ADHD symptoms to parental stress, with functional impairment and family functioning specified as mediators. Results Examining child- and family-related factors separately, child ADHD symptoms indirectly influenced parental stress via functional impairment, whereas parental ADHD symptoms significantly influenced parental stress both directly and indirectly via family functioning. In the integrated model examining both child- and family-related factors concurrently, the direct and indirect pathways from parental ADHD symptoms to parental stress via family functioning remained significant, but not the pathway from child ADHD symptoms to parental stress via functional impairment. Conclusions Functional impairment, parental ADHD, and family functioning, rather than child ADHD symptoms, are key determinants of parental stress in families of children with ADHD. These factors should be routinely assessed and targeted to alleviate parental stress more effectively than focusing on child ADHD symptoms alone.